Development of Perception-Focused Nutrition Education Material for Mothers of Children in Early Childhood - Noor, Remesah; Khurshid, Faiza; Arshad, Qurat-ul-ain; Qamar, Ujala; Yousaf, Fabia; Akbar, Javeria; Tanweer, Afifa (Nurture, 2022)
Purpose: Mothers play a crucial role in shaping the eating behavior of their children. Several studies have shown that mothers misperceive the diet quality, total energy intake, and portion sizes of their children. This misperception leads to overestimation or even underestimation of their children’s dietary intake which can have a detrimental effect on their health. Mothers associate a chubby child with good health and have a lot of emotional investment related to the amount of food their child ate. Design/Methodology/Approach: Even though past research articles acknowledge the existence of these perceptions, nutrition education material that could target these misperceptions has not been developed. The first step was to conduct a needs assessment and the second was to develop perception-focused nutrition education material. Findings: Three themes were identified by conducting a needs assessment and six themes were identified by going through research articles from the past. These nine themes identified were then organized and developed into three lesson plans with specific objectives. Practice implications: The perception-focused nutrition education material, thus developed, can be delivered to mothers through oral and visual aids. Through our developed nutrition educational material, future researchers will be able to test the perceptions of mothers regarding their child’s diet.